PREDICTING PRIVATE SAVING WITHIN MALAY COMMUNITY - Mei Teh Goi; Mohd Rizal Palil; Nor Hazila Mohd Zain; Nor Hasikin Mamat (Asian Academy of Management Journal, 2019)
Few reports have indicated that majority of Malaysians do not save enough for retirement and Malays are less likely to save money as compared to other races in Malaysia. A lot of attention has been given to the link between financial literacy and saving thus neglecting other factors that are closely related to individuals. According to Bandura’s (1977) theory, financial behaviour is closely related to personal factors such as individual characteristic, cognitive ability, self-efficacy, and religious faith. Therefore, this study aims to examine all the factors predicting private saving. Using 224 Malay respondents, logistic regression analysis was conducted. This study found that parents and religious faith significantly predicted the likelihood of private saving, but individual characteristic, cognitive ability, and self-efficacy did not significantly predict the likelihood of private saving. Thus, this study recommends using parents and religious officers to guide the Malay communities in their private saving.